Slurry and powder for sealing coating as well as preparation method and application of slurry and powder

By adopting multi-variable rare earth modified zirconia powder and high-temperature sintering and plasma spheroidization processes, a powder for sealing coating with a porous structure was prepared, which solved the insufficient performance of the existing coating in high temperature and water vapor corrosion, and achieved the improvement of high temperature thermal stability and corrosion resistance.

CN119569454AInactive Publication Date: 2025-03-07辽宁材料实验室
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510071350.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-temperature sealing coatings have shortcomings in their high temperature resistance and water vapor corrosion resistance, which are difficult to meet the high-temperature environment needs of hydrogen-burning engines.

Method used

Multi-various rare earth modified zirconia powder is used and combined with high-temperature sintering and plasma spheroidization process to prepare powder for sealing coating with a porous structure, and a pore-forming agent is added during the granulation process to improve the pore uniformity and binding force of the coating.

Benefits of technology

The high-temperature thermal stability and water vapor corrosion resistance of the coating are improved, ensuring that the coating does not peel off in a high-temperature environment, and meeting the high-temperature sealing needs of hydrogen-fueling engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569454A_ABST
    Figure CN119569454A_ABST
Patent Text Reader

Abstract

The invention provides slurry and powder for a seal coating as well as a preparation method and application of the slurry and the powder. The formula of the slurry for the seal coating adopts multi-element rare earth modified zirconium oxide, so that the high-temperature thermal stability of the slurry is improved, and the slurry has no phase change at 1200 DEG C. When the slurry for the sealing coating is used as a raw material to prepare powder for the sealing coating, a method of combining high-temperature sintering with a plasma spheroidizing process is adopted, a pore-forming agent is added again in the granulation process, a structure with a loose and porous interior can be formed after high-temperature sintering, and then a powder structure with a smooth and compact surface is obtained through plasma densification treatment. And uniformly mixing the powder structure with the compact surface and the loose and porous interior with boron nitride powder and a pore-forming agent to obtain the powder for the sealing coating. The sealing coating prepared from the powder for the sealing coating in a plasma spraying mode has a porous structure, is resistant to high temperature and water vapor corrosion, good in coating binding force, uniform in pore distribution and good in thermal stability and does not peel off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a slurry and powder for sealing coating, and a preparation method and application thereof. Background Art

[0002] Hydrogen-fired gas turbines are the development trend in the future in the fields of aviation, electricity, energy, etc. The application of hydrogen-fired gas turbines can increase the renewable energy rate and reduce CO 2 The world's major gas turbine manufacturers have all made hydrogen fuel gas turbine technology a research and development priority.

[0003] In the design and manufacture of gas turbines, reducing the clearance at the tip of the turbine blades is one of the effective ways to improve the efficiency of the gas turbine. Spraying a high-temperature abradable sealing coating on the inner wall of the stator casing is of great significance for improving the efficiency of the gas turbine and protecting the blades and casing from scratches. The inner wall of the turbine casing of a hydrogen-fired gas turbine matches the tip of the rotor blades and is subjected to high temperatures and blade tip scratches. Spraying a layer of abradable sealing coating material on the inner wall can avoid wear on the rotor blade tips and ensure the working efficiency of the turbine. At the same time, it establishes a barrier between high temperature and harsh environments (corrosive media, high-speed airflow erosion, etc.), preventing or reducing the impact of the environment, especially water vapor erosion, on the performance of high-temperature structural materials, and improving their high-temperature stability. This type of high-temperature sealing coating material and preparation technology is a hot spot and difficulty in research at home and abroad.

[0004] The combustion environment of hydrogen-fired gas turbines is special. The results of relevant foreign research show that in a hydrogen-fired environment, hydrogen-fueled gas turbines produce a large amount of water vapor after combustion. If high-temperature components are exposed to high-temperature water vapor for a long time, material performance degradation and failure will occur. Therefore, it is key to develop a new type of material to achieve a breakthrough in the core technology of wear resistance and high-temperature water vapor corrosion resistance. Summary of the invention

[0005] The invention provides a slurry and powder for sealing coating, a preparation method and application thereof, aiming to solve the problem that the existing sealing coating has poor high temperature resistance and water vapor corrosion resistance.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a sealing coating slurry, which comprises a powder mixture, gum arabic, ammonium citrate, a first pore-forming agent and deionized water, wherein the mass ratio of the powder mixture to gum arabic, ammonium citrate, the first pore-forming agent and deionized water is 1: (0.01-0.02): (0.01-0.02): (0.01-0.06): (0.3-1.5); wherein the powder mixture comprises Y 2 O 3 Powder, ZrO 2 Powder, Gd2 O 3 Powder and Yb 2 O 3 Powder, the Y 2 O 3 Powder, ZrO 2 Powder, the Gd 2 O 3 Powder and Yb 2 O 3 The molar ratio between the powders is (4-10):1:(1-6):(1-6).

[0008] The second aspect of the present invention provides a method for preparing the above-mentioned sealing coating slurry, the preparation method comprising: dissolving gum arabic in deionized water to obtain a gum arabic aqueous solution; 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 The powder, the gum arabic aqueous solution, ammonium citrate, the first pore-forming agent and deionized water are mixed by ball milling, and the mixture is evenly mixed and then sieved to obtain the slurry for the sealing coating.

[0009] The third aspect of the present invention provides a powder for sealing coating, the powder for sealing coating comprising an inner core layer and a coating layer coated outside the inner core layer; the chemical formula of the inner core layer is (4-10)Y 2 O 3 ZrO 2 (1~6)Gd 2 O 3 (1~6)Yb 2 O 3 The inner core layer is made of the sealing coating slurry as described above; the coating layer includes BN powder and a second pore-forming agent; the mass ratio of the coating layer to the inner core layer is (0.01-0.1):1.

[0010] Further, the added amount of the BN powder is between greater than 0 and less than or equal to 5% of the mass of the inner core layer; optionally, the added amount of the second pore-forming agent is between greater than 0 and less than or equal to 5% of the mass of the inner core layer.

[0011] Optionally, the amount of the BN powder added is between greater than 0 and less than or equal to 5% of the mass of the inner core layer; Optionally, the amount of the second pore-forming agent added is 1% to 10% of the mass of the inner core layer;

[0012] Furthermore, the powder for sealing coating is porous and has a spherical structure with a single pore size of <100 μm; the particle size of the powder for sealing coating is 10 μm to 176 μm, and its fluidity is <70s / 50g.

[0013] Furthermore, the Y 2 O 3 The purity of the powder is ≥99.9%, the particle size is D 50 0.5 μm to 2 μm; the ZrO 2 The purity of the powder is ≥99.9%, the particle size is D 50 is 0.5 μm to 2 μm; the Gd 2 O 3 Powder purity ≥99.9%, particle size D 50 0.2μm~2μm; the Yb 2 O 3 Powder purity ≥99.9%, particle size D 50 0.2μm~2μm; Optionally, the BN powder has a purity of ≥99.9% and a particle size D 50 1 μm to 10 μm; Optionally, the first pore-forming agent and the second pore-forming agent are both agglomerated, with a purity of ≥99.9% and a particle size D 50 It is 20μm~50μm.

[0014] Furthermore, both the first pore-forming agent and the second pore-forming agent are organic lipid materials that can be completely volatilized under a temperature environment of 500° C. to 1000° C.

[0015] Furthermore, the first pore-forming agent and the second pore-forming agent both include one or more of polyphenylene ester, phenolic resin, and polystyrene.

[0016] The fourth aspect of the present invention provides a method for preparing the above-mentioned sealing coating powder, characterized in that the preparation method comprises: step one, preparing the sealing coating slurry; step two, pouring the sealing coating slurry into a stirring device, using the operating parameters of the spray granulation tower inlet temperature of 200°C to 250°C, the outlet temperature of 90°C to 120°C, the atomizing disk speed of 11000r / min to 15000r / min, the feed rate of 5L / h to 10L / h, and atomizing and granulating with deionized water, and then drying and sieving to obtain a powder; step three, placing the powder in a sintering container, first heating it to 450°C to 550°C at a heating rate of 3°C / min to 5°C / min, and keeping it warm. 0.5h~1.0h, then continue to heat up to 900℃~1100℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 0.5h~1.0h, and finally continue to heat up to 1300℃~1500℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 2h~10h for sintering treatment to obtain sintered powder; Step 4, plasma spheroidization treatment of the sintered powder with a spheroidizing power of 40Kw~60Kw and a processing capacity of 2Kg / h~3Kg / h to obtain plasma spheroidized powder; Step 5, mechanically mix the plasma spheroidized powder with BN powder and pore-forming agent through a dry mixing device to obtain the powder for sealing coating. It can be understood that the slurry for sealing coating in step 1 can be prepared by the preparation method of the slurry for sealing coating provided above, or it can be prepared by other methods.

[0017] Preferably, in step 1, when the method for preparing the sealing coating slurry provided above is adopted, the mass fraction of the gum arabic aqueous solution in step 1 is 5% to 10%; the medium used for the ball milling is silicon nitride balls or zirconium oxide balls, and the ball-to-material ratio is (2 to 3): 1; the mixing time of the ball milling is 6h to 48h, the rotation speed is 30Hz to 40Hz, and the slurry after mixing is passed through a 120-mesh sieve; optionally, in step 2, the lining of the stirring device is polyurethane or nylon material; the rotation speed of the atomizing disk is 15000r / min, and the corresponding frequency is 30Hz; the parameters of the drying are: drying at 90℃ to 110℃ for 1h to 4h h; the mass ratio of the deionized water for atomization granulation to the mass of the inner core layer is (0.5-2):1; optionally, in step three, the temperature is increased to 500°C at a heating rate of 5°C / min, kept warm for 1h, then continued to be heated to 1000°C at a heating rate of 5°C / min, kept warm for 1h, and finally continued to be heated to 1300°C-1400°C at a heating rate of 5°C / min, and kept warm for 4h; optionally, in step five, the mass ratio of the plasma spheroidized powder to the BN powder is 1:(0.005-0.01), and the mass ratio of the plasma spheroidized powder to the second pore-forming agent is 1:(0.02-0.05).

[0018] A fifth aspect of the present invention provides the use of the sealing coating powder as described above in the field of hydrogen combustion engines.

[0019] The high-temperature sealing coating in the prior art is mostly prepared by high-temperature sintering of yttria-stabilized zirconia (YSZ) powder. The obtained sealing coating has the disadvantages of uneven porosity, high hardness, poor high-temperature thermal stability of the coating, and easy peeling and failure. Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0020] The present invention provides a sealing coating slurry, powder, and a preparation method and application thereof. The sealing coating slurry adopts multi-component rare earth modified zirconium oxide in the formula, which improves its high-temperature thermal stability and has no phase change at 1200°C. When the sealing coating powder is prepared using the sealing coating slurry as a raw material, a method combining high-temperature sintering and plasma spheroidization process is adopted, and a pore-forming agent is added again during the granulation process. After high-temperature sintering, an internal loose and porous structure can be formed, and then a plasma densification treatment is performed to obtain a powder structure with a smooth and dense surface. The powder structure with a dense appearance and a loose and porous interior is then mixed evenly with boron nitride (BN) powder and a pore-forming agent to obtain the sealing coating powder of the present invention. The sealing coating prepared by plasma spraying using the sealing coating powder has a porous structure, is resistant to high temperature and water vapor corrosion, has good coating adhesion, is evenly distributed in pores, and has good thermal stability and does not peel off. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.

[0022] Figure 1 This is a SEM photograph of the powder for sealing coating in Example 1 of the present invention;

[0023] Figure 2 This is a SEM photograph of the powder for sealing coating in Example 2 of the present invention;

[0024] Figure 3 This is a SEM photograph of the powder for sealing coating of Example 3 of the present invention;

[0025] Figure 4 The figure shows the morphology of a sealing coating prepared using the sealing coating powder of Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The inventors found that the ceramic material used for traditional high-temperature sealing coatings is mainly YSZ powder, which is used to prepare coatings by atmospheric plasma spraying. Most of the YSZ powders used are solid structures. The powder materials with high density and solid structures are not easy to melt during the spraying process. The prepared coatings are hard and difficult to scrape, which can easily wear the blades, and even cause the coating to fall off, causing the rear rotor blades to be damaged. Moreover, this type of coating has insufficient resistance to high-temperature water vapor corrosion. In the field of YSZ ceramic material research, some people use 8-11% mol yttria-stabilized zirconia as the main phase, and prepare block materials by adding different proportions of Ni, BN and polyphenylene ester using solid phase sintering method. The porosity, hardness and other tests of the ceramic blocks and sprayed coatings are carried out. The results show that the coating bonding strength is less than 5MPa, the coating peels off internally, and the thermal shock resistance to 1000℃ is also poor, which cannot meet the requirements of sealing coatings above 1000℃. Someone used nanocomposite structure coating technology to prepare 8YSZ nanostructured abradable sealing coating and conducted thermal shock and mechanical properties tests. The results showed that the nanoparticles in the coating structure can improve porosity, reduce hardness and enhance tensile strength, but the thermal corrosion resistance of the nanostructured coating is not ideal. The above research results show that it is difficult to simultaneously meet the three performance requirements of hardness, bonding strength and abradability by only adjusting the porosity, and the operating temperature of the YSZ material does not meet the design requirements of the new hydrogen-fired engine.

[0027] Based on this, the sealing coating powder provided by the present invention adopts multi-rare earth doped zirconia to increase the material use temperature, and at the same time, through the addition of lubricating phase materials and microstructure regulation, it has both high temperature resistance and wear resistance.

[0028] The present invention is described in detail below in conjunction with specific implementation modes.

[0029] Example 1: Example 1 provides a powder for sealing coating and a preparation method thereof.

[0030] The sealing coating powder of Example 1 is composed of Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 Powder, gum arabic, polyphenyl ester, BN, ammonium citrate and deionized water; Y 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 9:1; Gd 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 5:1; Yb 2 O 3 Powder and ZrO2 The molar ratio of the powder is 5:1; the amount of BN powder added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 1% of the total mass of the powder; the amount of pore-forming agent added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 4% of the total mass of the powder; the addition amount of gum arabic is 1% of the total mass of the above powder; the addition amount of ammonium citrate is 1.5% of the total mass of the above powder; the ratio of water to the total mass of all powders and gum arabic and ammonium citrate is 0.6:1.

[0031] The method for preparing the powder for sealing coating of Example 1 is carried out according to the following steps:

[0032] 1. Grinding and pulping: ① Dissolve gum arabic in 80℃ deionized water to obtain a 10% gum arabic aqueous solution; ② 2 O 3 Powder, ZrO 2 Powder, Yb 2 O 3 Powder, Gd 2 O 3 The powder, pore-forming agent (phenolic resin), gum arabic aqueous solution, ammonium citrate and deionized water were ball-milled in a planetary mill for 24 hours. The ball-milling medium was zirconia balls, the ball-to-material ratio was 2:1, the planetary mill speed was 40 Hz, and after mixing, the mixture was sieved through a 120-mesh sieve to obtain a slurry. The slurry was tested with a 4-mesh viscosity cup and the flow rate was 11 seconds.

[0033] 2. Atomization granulation: put the slurry obtained in step 1 into a stirring container, set the inlet and outlet temperatures of the centrifugal spray granulation tower to 220°C, the outlet temperature to 100°C, the atomizing disk speed to 12000r / min, the feed rate to 8L / h, and dry the powder after spray granulation at 100°C for 4h, then pass through a 150-mesh sieve to obtain the granulated powder.

[0034] 3. Sintering: put the powder obtained in step 2 into a corundum crucible and sinter it at 1300°C, first heat it to 500°C at a heating rate of 5°C / min, keep it warm for 1h, then heat it to 1300°C at a heating rate of 10°C / min, keep it warm for 4h, and obtain the sintered multi-component rare earth modified zirconia powder.

[0035] 4. Plasma spheroidization: The powder obtained in step 3 is subjected to plasma spheroidization treatment, the equipment power is 40Kw, and the feed rate is 2Kg / h to obtain plasma densified powder.

[0036] 5. Dry mixing: Mix the powder obtained in step 4 with BN powder and polyphenyl ester, with BN powder accounting for 0.6% of the total mass of the mixed powder and polyphenyl ester powder accounting for 4% of the total mass of the powder. Use a V-type mixer to mix 2 kg of powder each time. Sieve the mixed powder through a 120-mesh sieve to obtain multi-component rare earth modified zirconia powder for high-temperature sealing coating.

[0037] Figure 1 This is a SEM photograph of the powder for sealing coating in Example 1 of the present invention; Figure 4 The morphology of the sealing coating prepared by using the powder of Example 1 of the present invention. Figure 1 It can be seen that the powder surface after plasma densification treatment is smooth and has good sphericity, which is beneficial to the spraying process. Figure 4 It can be seen that the prepared sealing coating has uniform pores and each layer is tightly bonded.

[0038] Example 2: Example 1 provides a powder for sealing coating and a preparation method thereof.

[0039] The powder formulation for sealing coating of Example 2, Y 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 6:1; Gd 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 4:1; Yb 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 5:1; the amount of BN powder added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 1% of the total mass of the powder; the amount of pore-forming agent added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 The amount of gum arabic added is 1% of the total mass of the above powders; the amount of ammonium citrate added is 1.5% of the total mass of the above powders; the ratio of water to the total mass of all powders and gum arabic and ammonium citrate is 0.6:1.

[0040] The preparation method of the sealing coating powder of Example 2 is carried out according to the following steps:

[0041] 1. Grinding and pulping: ① Dissolve gum arabic in 80℃ deionized water to obtain a 10% gum arabic aqueous solution; ② 2 O 3 Powder, ZrO 2 Powder, Yb 2 O 3 Powder, Gd 2 O 3 Powder, pore-forming agent (phenolic resin and polystyrene mixed in a ratio of 1:1), gum arabic aqueous solution, ammonium citrate and deionized water were ball-milled in a planetary mill for 24 hours. The ball-milling medium was zirconia balls, the ball-to-material ratio was 2:1, the planetary mill speed was 40 Hz, and after mixing, the mixture was sieved through a 120-mesh sieve to obtain a slurry. The slurry was tested with a 4-mesh viscosity cup and the flow rate was 12 seconds.

[0042] 2. Atomization granulation: put the slurry obtained in step 1 into a stirring container, set the inlet and outlet temperatures of the centrifugal spray granulation tower to 220°C, the outlet temperature to 100°C, the atomizing disk speed to 14000r / min, the feed rate to 8L / h, and dry the powder after spray granulation at 100°C for 4h, then pass through a 150-mesh sieve to obtain the granulated powder.

[0043] 3. Sintering: put the powder obtained in step 2 into a corundum crucible and sinter it at 1400°C, first heat it to 500°C at a heating rate of 5°C / min, keep it warm for 1h, then heat it to 1400°C at a heating rate of 10°C / min, keep it warm for 4h, and obtain the sintered multi-component rare earth modified zirconia powder.

[0044] 4. Plasma spheroidization: The powder obtained in step 3 is subjected to plasma spheroidization treatment, with an equipment power of 45Kw and a feed rate of 2Kg / h to obtain a plasma densified powder.

[0045] 5. Dry mixing: Mix the powder obtained in step 4 with BN powder and polyphenyl ester, with BN powder accounting for 1% of the total mass of the mixed powder and polyphenyl ester powder accounting for 4% of the total mass of the powder. Use a V-type mixer to mix 2 kg of powder each time. Sieve the mixed powder through a 120-mesh sieve to obtain multi-component rare earth modified zirconia powder for high-temperature sealing coating.

[0046] Figure 2 This is a SEM photo of the powder for sealing coating of Example 2 of the present invention. Figure 2 It can be seen that with the appropriate increase of plasma densification power, the powder surface becomes denser and smoother, and the inside of the powder maintains a loose porous structure. This structural feature is conducive to the formation of a sealing coating with good bonding strength and uniform pores.

[0047] Example 3: Example 1 provides a powder for sealing coating and a preparation method thereof.

[0048] The powder formulation for sealing coating of Example 3, Y 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 5:1; Gd 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 2:1; Yb 2 O 3 Powder and ZrO 2 The molar ratio of the powder is 3:1; the amount of BN powder added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 0.5% of the total mass of the powder; the amount of pore-forming agent added is Y 2 O 3 Powder, ZrO 2 Powder, Gd 2 O 3 Powder, Yb 2 O 3 The amount of gum arabic added is 4.5% of the total mass of the powder; the amount of ammonium citrate added is 1% of the total mass of the above powder; the ratio of water to the total mass of all powders and gum arabic and ammonium citrate is 0.8:1.

[0049] The preparation method of the powder for sealing coating of Example 3 is carried out according to the following steps:

[0050] 1. Grinding and pulping: ① Dissolve gum arabic in 80℃ deionized water to obtain a 10% gum arabic aqueous solution; ② 2 O 3 Powder, ZrO 2 Powder, Yb 2 O 3 Powder, Gd 2 O 3 The powder, pore-forming agent (polyphenyl ester), gum arabic aqueous solution, ammonium citrate and deionized water were ball-milled in a planetary mill for 24 hours. The ball-milling medium was zirconia balls, the ball-to-material ratio was 2:1, the planetary mill speed was 40 Hz, and after mixing, the mixture was sieved through a 120-mesh sieve to obtain a slurry. The slurry was tested with a 4-mesh viscosity cup and the flow rate was 11 seconds.

[0051] 2. Atomization granulation: put the slurry obtained in step 1 into a stirring container, set the inlet and outlet temperatures of the centrifugal spray granulation tower to 220°C, the outlet temperature to 100°C, the atomizing disk speed to 13000r / min, the feed rate to 8L / h, and dry the powder after spray granulation at 100°C for 4h, then pass through a 150-mesh sieve to obtain the granulated powder.

[0052] 3. Sintering: put the powder obtained in step 2 into a corundum crucible and sinter it at 1400°C, first heat it to 500°C at a heating rate of 5°C / min, keep it warm for 1h, then heat it to 1400°C at a heating rate of 10°C / min, keep it warm for 4h, and obtain the sintered multi-component rare earth modified zirconia powder.

[0053] 4. Plasma spheroidization: The powder obtained in step 3 is subjected to plasma spheroidization treatment, the equipment power is 55Kw, and the feed rate is 2Kg / h to obtain plasma densified powder.

[0054] 5. Dry mixing: Mix the powder obtained in step 4 with BN powder and polyphenyl ester, with BN powder accounting for 1% of the total mass of the mixed powder and polyphenyl ester powder accounting for 4% of the total mass of the powder. Use a V-type mixer to mix 2 kg of powder each time. Sieve the mixed powder through a 120-mesh sieve to obtain multi-component rare earth modified zirconia powder for high-temperature sealing coating.

[0055] Figure 3 This is a SEM photo of the powder for sealing coating of Example 3 of the present invention. Figure 3 It can be seen that further increasing the plasma densification power can significantly improve the powder density, and the prepared powder fluidity and bulk density will also be significantly improved. The interior still maintains a loose porous structure, and a porous sealing coating can be obtained after plasma spraying.

[0056] The density and fluidity of the powder for high temperature sealing coating of the novel structure obtained in Examples 1 to 3 were tested, and the powder density and fluidity data shown in Table 1 were obtained; the comparative example is the relevant indicators of a certain brand of powder for sealing coating.

[0057] Table 1 Powder density and fluidity data

[0058] Powder properties Example 1 Example 2 Example 3 Comparative Example <![CDATA[Bulk density (g / cm 3 )]]> 2.06 2.20 3.10 1.96 <![CDATA[Tap density (g / cm 3 )]]> 2.34 2.48 3.47 2.25 Angle of repose(°) 27 26 25 27 Flow rate (s / 50g) 53.2 43.5 33.4 48.0

[0059] As can be seen from Table 1, the density of the prepared powder after sintering and plasma densification is greater than that of the control example, and the powder fluidity is better than that of the control example, meeting the requirements for the preparation of sealing coatings. Powders with different morphologies and densities can be obtained by adjusting the process parameters of granulation and plasma spheroidization, thereby preparing coatings with different properties.

[0060] Table 2 shows the relevant properties of the coatings obtained by plasma spraying the powders prepared in Examples 1 to 3; the comparative data are the relevant indicators of the coatings prepared using a certain brand of powder in Table 1.

[0061] Table 2 Coating properties

[0062] Coating performance Example 1 Example 2 Example 3 Comparative Example Binding strength (MPa) 7.81 8.15 9.33 7.23 Hardness (HR 15Y) 81.9 82.8 88.5 90.2 Deposition efficiency (mm / pass) 0.009 0.01 0.012 0.009

[0063] It can be seen from Table 2 that the coatings prepared using the powders of Examples 1 to 3 have higher bonding strength than the comparative example, and have moderate hardness, slightly lower than the comparative example coating. The deposition efficiency of the coatings is higher than that of the comparative example. The prepared coatings undergo no phase change after heat treatment at 1300°C for 100 hours, indicating that the prepared powders meet the requirements for preparing high-temperature sealing coatings.

[0064] Those skilled in the art will appreciate that the above embodiments are specific examples of the present invention, and in practical applications, various changes may be made to the embodiments in form and detail without departing from the spirit and scope of the present invention. Any person skilled in the art may make changes and modifications without departing from the spirit and scope of the present invention, and therefore the scope of protection of the present invention shall be subject to the scope defined in the claims.

Claims

1. A slurry for sealing coating, characterized in that: The sealing coating slurry comprises a powder mixture, gum arabic, ammonium citrate, a first pore-forming agent and deionized water, wherein the mass ratio of the powder mixture to gum arabic, ammonium citrate, the first pore-forming agent and deionized water is 1: (0.01-0.02): (0.01-0.02): (0.01-0.06): (0.3-1.5); Wherein, the powder mixture includes Y2O3 powder, ZrO2 powder, Gd2O3 powder and Yb2O3 powder, and the molar ratio between the Y2O3 powder, ZrO2 powder, the Gd2O3 powder and the Yb2O3 powder is (4-10):1:(1-6):(1-6).

2. The method for preparing the sealing coating slurry according to claim 1, characterized in that: The preparation method comprises: Gum arabic is dissolved in deionized water to obtain a gum arabic aqueous solution; Y2O3 powder, ZrO2 powder, Gd2O3 powder, Yb2O3 powder, gum arabic aqueous solution, ammonium citrate, a first pore-forming agent and deionized water are mixed by ball milling, and the mixture is evenly mixed and then sieved to obtain the slurry for the sealing coating.

3. A powder for sealing coating, characterized in that: The powder for sealing coating comprises an inner core layer and a coating layer coated outside the inner core layer; the chemical formula of the inner core layer is (4-10)Y2O3ZrO2(1-6)Gd2O3(1-6)Yb2O3, and the inner core layer is made of the sealing coating slurry as claimed in claim 1; the coating layer comprises BN powder and a second pore-forming agent; the mass ratio of the coating layer to the inner core layer is (0.01-0.1):

1.

4. The sealing coating powder according to claim 3, characterized in that: The amount of the BN powder added is between greater than 0 and less than or equal to 5% of the mass of the inner core layer; Optionally, the added amount of the second pore-forming agent is between greater than 0 and less than or equal to 5% of the mass of the inner core layer.

5. The sealing coating powder according to claim 3, characterized in that: The powder for sealing coating is porous and has a spherical structure with a single pore size of less than 100 μm; the particle size of the powder for sealing coating is 10 μm to 176 μm, and its fluidity is less than 70 s / 50 g.

6. The sealing coating slurry according to claim 5, characterized in that: The purity of the Y2O3 powder is ≥99.9%, and the particle size is D 50 0.5μm~2μm; the purity of the ZrO2 powder is ≥99.9%, and the particle size D 50 0.5μm~2μm; the purity of the Gd2O3 powder is ≥99.9%, and the particle size D 50 0.2μm~2μm; the purity of the Yb2O3 powder is ≥99.9%, and the particle size D 50 0.2μm~2μm; Optionally, the BN powder has a purity of ≥99.9% and a particle size of D 50 1μm~10μm; Optionally, the first pore-forming agent and the second pore-forming agent are both agglomerated, with a purity of ≥ 99.9% and a particle size D 50 It is 20μm~50μm.

7. The sealing coating powder according to claim 3, characterized in that: The first pore-forming agent and the second pore-forming agent are both organic lipid materials that can be completely volatilized under a temperature environment of 500° C. to 1000° C.

8. The sealing coating powder according to claim 7, characterized in that: The first pore-forming agent and the second pore-forming agent both include one or more of polyphenylene ester, phenolic resin, and polystyrene.

9. The method for preparing a powder for sealing coating according to any one of claims 3 to 8, characterized in that: The preparation method comprises: Step 1, preparing the sealing coating slurry; Step 2: pour the sealing coating slurry into a stirring device, and perform atomization and granulation treatment with deionized water, and then dry and sieve to obtain a powder; Step 3, placing the powder in a sintering container, first heating the temperature to 450-550°C at a heating rate of 3-5°C / min, keeping the temperature for 0.5h-1.0h, then continuing to heat the temperature to 900-1100°C at a heating rate of 5°C / min-10°C / min, keeping the temperature for 0.5h-1.0h, and finally continuing to heat the temperature to 1300-1500°C at a heating rate of 5°C / min-10°C / min, keeping the temperature for 2h-10h, and sintering treatment is performed under the conditions of sintering to obtain a sintered powder; Step 4: performing plasma spheroidization treatment on the sintered powder with a spheroidizing power of 40Kw to 60Kw and a processing capacity of 2Kg / h to 3Kg / h to obtain plasma spheroidized powder; Step 5: Mechanically mix the plasma spheroidized powder, BN powder and pore-forming agent through a dry mixing device to obtain the powder for sealing coating.

10. Use of the sealing coating powder according to any one of claims 3 to 7 in the field of hydrogen combustion engines.

Citation Information

Patent Citations

  • Dysprosia stabilized zirconia abradable

    CN101125753A

  • Coated composite high-temperature abradable seal coating material and preparation method thereof

    CN102558931A

  • Multi-component rare earth oxide-doped modified YSZ thermal spraying powder and preparation method thereof

    CN106380210A

  • Nano mullite powder for plasma physical vapor deposition and preparation method of nano mullite powder

    CN111534796A

  • Coating material for thermal spray and fabrication method and coating method thereof

    KR1020120092227A